Anisotropy of Spin Relaxation in Metals - Zimmermann, Bernd; Mavropoulos, Phivos; Heers, Swantje; Long, Nguyen H.; Blügel, Stefan; Mokrousov, Yuriy (PHYSICAL REVIEW LETTERS, 2012)
The concept of anisotropy of spin relaxation in nonmagnetic metals with respect to the spin direction of the injected electrons relative to the crystal orientation is introduced. The effect is related to an anisotropy of the Elliott-Yafet parameter, arising from a modulation of the decomposition of the spin-orbit Hamiltonian into spin-conserving and spin-flip terms as the spin quantization axis is varied. This anisotropy, reaching gigantic values for uniaxial transition metals (e.g., 830% for hcp Hf) as density-functional calculations show, is related to extended ``spin-flip hot areas'' on the Fermi surface created by the proximity of extended sheets of the surface, or ``spin-flip hot loops'' at the Brillouin zone boundary, and has no theoretical upper limit. Possible ways of measuring the effect as well as consequences in application are briefly outlined.